2021
DOI: 10.1007/s00203-021-02248-z
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial properties of Allium sativum L. against the most emerging multidrug-resistant bacteria and its synergy with antibiotics

Abstract: Garlic has long been known as the most effective plant species in treatment of bacterial infections. Considering the vast potential of garlic as a source of antimicrobial drugs, this study is aimed to evaluate the antibacterial activity of Allium sativum extracts and their interactions with selected antibiotics against drug-sensitive and multidrug-resistant isolates of emerging bacterial pathogens that are frequently found in healthcare settings. As shown by the in vitro data obtained in this study, the whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 61 publications
2
28
0
Order By: Relevance
“…Antimicrobial activity against a wide range of microbes has been manifested by aqueous extracts of ginger, owing to its phenolic contents of therapeutic nature [ 4 ]. Allium sativum commonly known as garlic contains phenolic compounds exhibiting a broad-spectrum antibacterial activity even against MDR bacteria [ 5 ]. Allium sativum has exhibited broad-spectrum antibacterial activity against a number of Gram-positive and various Gram-negative bacteria [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobial activity against a wide range of microbes has been manifested by aqueous extracts of ginger, owing to its phenolic contents of therapeutic nature [ 4 ]. Allium sativum commonly known as garlic contains phenolic compounds exhibiting a broad-spectrum antibacterial activity even against MDR bacteria [ 5 ]. Allium sativum has exhibited broad-spectrum antibacterial activity against a number of Gram-positive and various Gram-negative bacteria [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bactericidal activity 1 (3 mL:1), 2 (6 mL:1), 3 (12 mL:1),4 Ciprofloxacin,5 DIWConclusionsBactericidal potential of CuO NPs doped with Zingiber officinale and Allium sativum extracts against pathogenic E. coli was evaluated in this study, produced with the aim of alternate, economical and effective antimicrobials. The significant role of phytochemical ingredients of ZO and AS extracts was revealed in the biogenic synthesis of CuO NPs while synergistic effects of flavonoids with CuO were found to be concentration-dependent exploiting the bactericidal potential against pathogenic E. coli.…”
mentioning
confidence: 99%
“…It is known that Bacillus anthrasis causing anthrax infections is the most susceptible bacteria to garlic. [59] Amir Sasan et al [60] concluded the anti-bacterial activities of Aqueous garlic extract in hamburger S.aureus. In addition, not only as a taste but as a natural component for hamburgers may be used garlic aqueous extract.…”
Section: Effects Of Garlic On the Immune Systemmentioning
confidence: 99%
“…Owing to the outstanding advantages, such as the nature of the original compounds, the functionality of a lot of active ingredients, and the low cost of a wide range of sources, plant-derived medicines are becoming more and more popular with consumers worldwide. In the current era of widespread antibiotic resistance, plant-derived medicines such as garlic have remarkably persisted over time and continue to be used today for indications similar to those described historically, which can be used as alternative antibiotic resources [ 5 ]. In addition, plant-derived medicines as functional foods have made a significant contribution to human or animal health [ 6 ].…”
Section: Introductionmentioning
confidence: 99%